The Effectiveness of Cognitive Behavioral Counseling Theory with Relaxation Techniques in Managing Student Burnout and Stress - Oktavia Christin Angkouw; I Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2025)
A significant increase in students' levels of boredom and learning stress has become a serious problem that can hinder the effectiveness and quality of the learning process in schools. This condition requires appropriate intervention efforts to help students manage stress and improve their readiness to learn. This study aims to test the effectiveness of cognitive behavioural counselling combined with relaxation techniques in reducing students' levels of boredom and learning stress. This study employs a quasi-experimental approach with a One Group Pretest-Posttest design. The research subjects consisted of 30 students selected through purposive sampling based on specific criteria. Data were collected using a Likert scale questionnaire and analysed using a Paired Sample t-test to determine significant differences between the pre- and post-treatment conditions. The analysis results showed significant differences in levels of boredom and learning stress before and after the counselling intervention. These findings indicate that relaxation techniques in cognitive behavioural counselling are effective in reducing learning fatigue and stress, as well as improving students' calmness and mental readiness to participate in the learning process. The implications of this study emphasise the importance of applying relaxation-based psychological interventions as a supporting strategy in creating a mentally and emotionally healthy learning environment.